AN ANALYSIS OF COLLEGE STUDENTS ABILITY TO DETECT FRAUD USING THE ASTIN I-E-O MODEL - Mukhotib, Ahmad Atho'; Hartiyah, Sri; ., Romandhon; Mas’ud, Abdurrahman (JURNAL AKUNTANSI DAN AUDITING, 2024)
This study aims to determine the ability of students to detect fraud by using the variables of student motivation, academic achievement, involvement in Auditing lectures, and the ability to detect fraud. The population in this study were 139 students of the Accounting Study Programme, Faculty of Economics and Business, Al-Qur'an University of Science class of 2019. This study used the total sampling method and was collected through a questionnaire with the help of the Google Forms platform, obtaining a total of 75 students who responded. The analysis technique used is path analysis with the help of SPSS software version 25. The results of this study indicate that student motivation has a positive effect on Auditing lecture involvement, and academic achievement has no effect on Auditing lectures. Meanwhile, Auditing lecture involvement has a positive effect on the ability to detect fraud, and student motivation and academic achievement do not affect the ability to detect fraud.